Evaluation of tetramethylammonium acetate as corrosion suppressor for flow assurance applications - Qasim, A. (Elsevier Ltd, 2020)
For flow assurance applications, various chemicals are used in the oil and gas industry in order to mitigate corrosion. Among corrosion suppressing compounds, quaternary ammonium salts (QASs) find an exceptional usage as these relatively long chain compounds adsorb onto the surface of the pipeline. The formation of protective layer by adsorbing on the surface prevents corrosion. In this work, tetramethylammonium acetate (TMAAc) which is QAS is evaluated as a corrosion controlling compound in saline environment using weight loss method. The weight loss experiments are performed with the solution concentrations of TMAAc at 0.01, 0.5, 1, 2, 5 and 10wt. Corrosion rate values are determined at these concentrations. It is observed that the corrosion with the increase in concentration of TMAAc, corrosion rate is also increased. Rate of metal corrosion varies from 0.068mm/yr to 0.176mm/yr in the range of 0.01-10wt. The minimum value of corrosion rate is found to be 0.068mm/yr at the sample concentration of 100ppm. It is concluded that at lower concentrations, TMAAc can find its application as a commercial corrosion inhibitor. Â© 2021 Elsevier Ltd.